Atherton–Todd reaction: mechanism, scope and applications - Le Corre, Stéphanie S.; Berchel, Mathieu; Couthon-Gourvès, Hélène; Haelters, Jean-Pierre; Jaffrès, Paul-Alain (Beilstein Journal of Organic Chemistry, 2014)
Initially, the Atherton–Todd (AT) reaction was applied for the synthesis of phosphoramidates by reacting dialkyl phosphite with a primary amine in the presence of carbon tetrachloride. These reaction conditions were subsequently modified with the aim to optimize them and the reaction was extended to different nucleophiles. The mechanism of this reaction led to controversial reports over the past years and is adequately discussed. We also present the scope of the AT reaction. Finally, we investigate the AT reaction by means of exemplary applications, which mainly concern three topics. First, we discuss the activation of a phenol group as a phosphate which allows for subsequent transformations such as cross coupling and reduction. Next, we examine the AT reaction applied to produce fire retardant compounds. In the last section, we investigate the use of the AT reaction for the production of compounds employed for biological applications. The selected examples to illustrate the applications of the Atherton–Todd reaction mainly cover the past 15 years.
Keywords: amphiphiles; flame retardant; lipid conjugates; organophosphorus; phosphoramidate; phosphate